THE APPLICATION OF LIMITATION PERIODS IN CASE OF SELF-DEFENSE OF RIGHTS - Gabuzyan, Kristine (State and Law, 2021)
The current article discusses the possibility and expediency of applying the limitation periods to such methods of coercive protection of rights as self-defense. The article reveals the uncertainty of the provisions of the civil code in relation to this issue and the associated risks. As a result, in order to fully achieve the purpose of the limitation periods, it is proposed to extend the application of limitation periods to the measures of self-defense, as well as to provide for appropriate mechanisms that will allow the debtor to defend his interests, referring to the limitation periods.
Keywords: limitation periods; self-defense of rights; judicial protection; unjust enrichment